2010
DOI: 10.1021/nn100400r
|View full text |Cite
|
Sign up to set email alerts
|

High Capacity and Excellent Stability of Lithium Ion Battery Anode Using Interface-Controlled Binder-Free Multiwall Carbon Nanotubes Grown on Copper

Abstract: We present a novel binder-free multiwall carbon nanotube (MWCNT) structure as an anode in Li ion batteries. The interface-controlled MWCNT structure, synthesized through a two-step process of catalyst deposition and chemical vapor deposition (CVD) and directly grown on a copper current collector, showed very high specific capacity, almost three times as that of graphite, excellent rate capability even at a charging/discharging rate of 3 C, and no capacity degradation up to 50 cycles. Significantly enhanced pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
134
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(148 citation statements)
references
References 44 publications
7
134
6
Order By: Relevance
“…CNTs are highlighted as the possible electrode materials [64][65][66][67]. The Al2O3-coated CNTs have been successfully prepared on a copper substrate and tested as a LIB anode [68].…”
Section: Al2o3mentioning
confidence: 99%
“…CNTs are highlighted as the possible electrode materials [64][65][66][67]. The Al2O3-coated CNTs have been successfully prepared on a copper substrate and tested as a LIB anode [68].…”
Section: Al2o3mentioning
confidence: 99%
“…by catalytic thermal CVD and demonstrated excellent properties for application in LIB electrodes [34]. An MWCNT grown on Cu anode showed very high specific capacity (for the second discharge cycle, it was 1,455 mAhg -1 ) and exceptional stability of the reversible capacity (~ 900 mAhg -1 ) at 1C rate, as presented in Figure 11.…”
Section: Brief Introduction To Carbon Nanotubesmentioning
confidence: 94%
“…In the past, our research team demonstrated outstanding performance of MWCNT-based binder-free anodes in terms of high specific capacity, excellent rate capability and extremely low or nil capacity degradation during long cycle operation [34][35]. However, carbon nano-materials are known as low-density materials that result in low volumetric capacity and low volumetric energy/power density.…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations